Effect of silicon addition on the growth and photosynthesis of Castanopsis hystrix in manganese stress - Linjuan HUANG; Zhangqiang TAN; Kang LEI; Linghui WANG; Wenhui SHEN; Weichao TENG (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2024)
Silicon (Si) plays important role in reducing the toxic effects of manganese (Mn) in plants, however, more research is needed to elucidate the photosynthetic response with different Si and Mn treatments. This study aimed to investigate the alleviating effect of Si on the growth and photosynthesis of Castanopsis hystrix (C. hystrix) under Mn stress. Seedlings were grown in pot experiments with five Mn levels (0, 200, 600, 1500, and 3000 mg·kg-1) and four Si levels (0, 115, 230, and 460 mg·kg-1). The results showed that three types of (positive, stagnant, and negative) growth of C. hystrix seedlings were observed among twenty treatments. Low concentrations of Si (Si ≤ 115 mg·kg-1) and Mn treatments (Mn ≤ 600 mg·kg-1) can stimulate a positive growth of seedlings by increasing net photosynthetic rate (Pn), transpiration rate (Tr), and stomatal conductance (Gs). The 230 mg·kg-1 Si with low concentration of Mn treatments can cause a stagnant growth of seedlings by increasing Gs, Tr and maximum photochemical efficiency of PSII (Fv/Fm) but decreasing intercellular carbon dioxide concentration (Ci). High concentrations of Si (Si ≥ 460 mg·kg-1) or Mn treatments (Mn ≥ 1500 mg·kg-1) treatments can cause negative growth of seedlings by decreasing photochemical quenching (qP), non-photochemical quenching (qN), Gs, Pn and pigment contents. The application of Si alleviated the stress induced by Mn and promoted the growth-defense regulation mechanism of seedlings to avoid stress. Hence, we concluded that the most suitable concentration of Si was 115 mg·kg-1 Si for C. hystrix’s growth under low Mn stress.